Le signorie dei Rossi di Parma tra XIV e XVI secolo - Arcangeli, Letizia (Reti Medievali E-Book, 2007)
This volume is devoted to one of the major aristocratic lineages of northern Italy in the later middle ages. The Rossi, whose political and social eminence dates back to the communal age, built in the Parmense a powerful lordship, based both on their estates and fortresses and on a vast patronage network spread over the territory and in the town: and the power of the family, though diminished after the crisis in the relations with the Sforza in 1482, was restored on partially different foundations during the Italian Wars. The essays collected in this book explore the complexity of the Rossi "little seignorial state", focusing on its internal constitution, on its exterior relations and on its artistic and cultural features between the mid-fourteenth and the early sixteenth century.